Factorization theory of root closed monoids of small rank. Issue 7 (3rd July 2017) - Coykendall, Jim; Oman, Greg
ABSTRACT: In this note, we investigate ideal and factorization-theoretic properties of some root closed cancellative commutative monoids of rank at most two.